2010
DOI: 10.1103/physrevlett.105.237601
|View full text |Cite
|
Sign up to set email alerts
|

kDependence of the Crystal-Field Splittings of4fStates in Rare-Earth Systems

Abstract: The occupation, energy separation, and order of the crystal-field-split 4f states are crucial for the understanding of the magnetic properties of rare-earth systems. We provide the experimental evidence that crystal-field-split 4f states exhibit energy dispersion in momentum space leading to variations of energy spacings between them and even of their energy sequence across the Brillouin zone. These observations were made by performing angle-resolved photoemission experiments on YbRh(2)Si(2) and properly simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 23 publications
4
52
0
Order By: Relevance
“…Our previous ARPES studies on structurally similar RET 2 Si 2 materials (RE=Eu, Yb and T=Co, Rh, Ir) demonstrated that cleavage always takes place between Si and RE layers leaving behind either a RE or a Si terminated surface2021222324. The covering of a RE plane with a Si−Rh−Si trilayer is usually sufficient to create a bulk-type chemical surrounding for the RE ions2526.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous ARPES studies on structurally similar RET 2 Si 2 materials (RE=Eu, Yb and T=Co, Rh, Ir) demonstrated that cleavage always takes place between Si and RE layers leaving behind either a RE or a Si terminated surface2021222324. The covering of a RE plane with a Si−Rh−Si trilayer is usually sufficient to create a bulk-type chemical surrounding for the RE ions2526.…”
Section: Resultsmentioning
confidence: 99%
“…This might be a consequence of the robust in-plane AFM order of the Ce moments along each Ce layer—in contrast to the ferromagnetic arrangement of the 4 f moments within the Eu planes in EuRh 2 Si 2 —canceling the exchange interaction between the Ce moments and the electrons in the surface state. A further signature of differing surface terminations shows up in a hole-like, linearly dispersing surface resonant band labelled by a sun-symbol around the point in the Si-terminated case2223, which is replaced by an intense, rocket-shaped feature (labelled by a triangle) below ∼0.5 eV BE for Ce termination. The Dirac cone (sun-symbol) arises from Rh 4 d states in the topmost Si−Rh−Si trilayer and has similarly been found in YbRh 2 Si 2 and EuRh 2 Si 2 (refs 21, 22, 23).…”
Section: Resultsmentioning
confidence: 99%
“…The c-f hybridization-derived electronic structure has been verified by ARPES studies [2][3][4][5][6][7][8][9][10][11][12][13] . However, most of those studies have been performed on the basis of the surface Brillouin zone (BZ) [2][3][4][5][6] or by using the 4d-4f resonant process [7][8][9] , in which k z (the momentum normal to surface) dependence on the electronic structure is neglected owing to its quasi-two-dimensionality. In general, ARPES along the bulk BZ with well-defined k z should be ideal for the three-dimensional materials.…”
mentioning
confidence: 98%
“…The angle resolved photoemission spectroscopy (ARPES) measurements on 2 2 YbRh Si revealed a very narrow 4f band near the Fermi energy [15]. It is an additional argument confirming the quasi-localized nature of the f-electron motion (in the case of absolutely localized electrons their width of energy band as a function of the wave vector reduces to zero).…”
Section: Crystal Electric Field and Magnetic Susceptibilitymentioning
confidence: 79%